Analisis Kinerja Pegawai di Kecamatan Ciputat Timur Kota Tangerang Selatan - Sandriane Meiladinov; Nida Handayani (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
East Ciputat District one of the government institutions that has the task of providing community services. In providing services, Ciputat Timur District still has several problems, namely that performance accountability is not yet optimal, the use of information technology has not been optimized to help the smooth running of services, and the pattern of training for officers is not yet oriented towards improving performance. The purpose of this research is to determine the current performance of employees in East Ciputat District, South Tangerang City. The research method used in this research is descriptive with a qualitative approach, with data collection techniques namely observation, interviews and documentation. This research is based on the theory of Employee Performance Indicators by Bernardin (2016), and found several findings that now East Ciputat District employees have experienced an increase in their performance. This is known from the quality of employee performance which satisfies community expectations, and also from employee responsiveness in resolving problems. Apart from that, employees can also responsibly complete 3 cycles of work activities, successfully achieve predetermined performance targets, as well as being disciplined in carrying out their main duties. Apart from that, the employees are agile and have good synergy in working.